α-Synuclein structural features inhibit harmful polyunsaturated fatty acid oxidation, suggesting roles in neuroprotection - De Franceschi, Giorgia (J Biol Chem, 2017)
α-Synuclein (aS) is a protein abundant in presynaptic nerve terminals in Parkinson disease (PD) and is a major component of intracellular Lewy bodies, the pathological hallmark of neurodegenerative disorders such as PD. Accordingly, the relationships between aS structure, its interaction with lipids, and its involvement in neurodegeneration have attracted great interest. Previously, we reported on the interaction of aS with brain polyunsaturated fatty acids, in particular docosahexaenoic acid (DHA). aS acquires an α-helical secondary structure in the presence of DHA and, in turn, affects DHA structural and aggregative properties. Moreover, aS forms a covalent adduct with DHA. Here, we provide evidence that His-50 is the main site of this covalent modification. To better understand the role of His-50, we analyzed the effect of DHA on aS-derived species: a naturally occurring variant, H50Q; an oxidized aS in which all methionines are sulfoxides (aS4ox); a fully lysine-alkylated aS (acetyl-aS); and aS fibrils, testing their ability to be chemically modified by DHA. We show, by mass spectrometry and spectroscopic techniques, that H50Q and aS4ox are modified by DHA, whereas acetyl-aS is not. We correlated this modification with aS structural features, and we suggest a possible functional role of aS in sequestering the early peroxidation products of fatty acids, thereby reducing the level of highly reactive lipid species. Finally, we show that fibrillar aS loses almost 80% of its scavenging activity, thus lacking a potentially protective function. Our findings linking aS scavenging activity with brain lipid composition suggest a possible etiological mechanism in some neurodegenerative disorders.